Pemahaman Terhadap Peran dan Fungsi Kholesterol dalam Rangka Kempanye Kecukupan Gizi Melalui Konsumsi Produk Hewani - Eka Handayanta (Caraka Tani: Journal of Sustainable Agriculture, 2007)
Material of animal food like as meat, milk and egg have the excess compared to material of vegetation food. The excess shown by nutrient content and vital function to the body. Therefore sufficiency gizi program is importance emboldened. But that way this program often burdened by less information, related to content cholesterol in the animal product that indicate as cause venous disease like as: Artherosclerosis, Coronary Heart Disease (CHD) and Stroke. Some research result shown that the consumption of animal product do not always increase plasma cholesterol blood. Imprecise thereby when decreasing or even fear to consume the animal product. The effort preventive must be require to decrease consume for consumer that have higher cholesterol. Inwrought effort as prevention can be conducted by arrange menu eat, regular sport and avoid the cigarette habit. Finally, campaign anti cholesterol shall be conducted by neglectlessly and wise so that gizi improvement program by the consumption of animal product can be succeed